2006
DOI: 10.1097/wnr.0b013e3280102ed4
|View full text |Cite
|
Sign up to set email alerts
|

Association of G72/G30 polymorphisms with early-onset and male schizophrenia

Abstract: To explore the e¡ect of G72/G30 polymorphisms on the clinical manifestations of schizophrenia, especially on the age at onset and sex of patients, we examined three single nucleotide polymorphisms in 216 schizophrenic patients and 321 healthy controls. Signi¢cant associations of schizophrenia with the A allele of rs947267 (P ¼ 0.012) and haplotype A-A-G (rs2391191-rs947267-rs778294) (P ¼ 0.008) were found in early-onset schizophrenic patients. So did the same allele (P ¼ 0.034) and haplotype (P ¼ 0.009) as men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Several studies were excluded because of sample duplication with another study (Yue et al, 2006), lack of sufficient data even after requesting informative data from the authors (Fallin et al, 2005;Goldberg et al, 2006;Hall et al, 2004;Nicodemus et al, 2007). M12, M15, M23 and M24 were excluded for BP because they were analyzed in only one or two studies (Schulze et al, 2005).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies were excluded because of sample duplication with another study (Yue et al, 2006), lack of sufficient data even after requesting informative data from the authors (Fallin et al, 2005;Goldberg et al, 2006;Hall et al, 2004;Nicodemus et al, 2007). M12, M15, M23 and M24 were excluded for BP because they were analyzed in only one or two studies (Schulze et al, 2005).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Shortly afterward, the G72/ G30 gene complex (G72 is now officially known as D-aminoacid oxidase activator, DAOA) was associated, independently, with each disorder (Chumakov et al, 2002;Hattori et al, 2003). An association has been reported in multiple independent studies (Addington et al, 2004;Chen et al, 2004;Fallin et al, 2005;Hall et al, 2004;Hong et al, 2006;Korostishevsky et al, 2004;Korostishevsky et al, 2006;Ma et al, 2006;Schulze et al, 2005;Schumacher et al, 2004;Wang et al, 2004;Williams et al, 2006;Yue et al, 2006;Yue et al, 2007;Zou et al, 2005). However, several studies did not find association with traditional BP or SCZ phenotype (Bakker et al, 2007;Goldberg et al, 2006;Liu et al, 2006;Mulle et al, 2005;Vilella et al, 2007;Wood et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen SNPs were genotyped across these four candidate genes in the Chinese Han population, which included 120 schizophrenia cases and 225 healthy controls. Prior reports have suggested that variations in the genes may be associated with increased risk of paranoid schizophrenia (Yue et al 2006(Yue et al , 2007Zhang et al 2004;Harrison and Owen 2003). Model 1: P(Disease|AAbb) = 0.02, P(Disease|AaBb) = 0.2, P(Disease|aaBB) = 0.02, and P(Disease|others) = 0; Model 2: P(Disease|AAbb) = 0.2, P(Disease|AaBb) = 0.2, P(Disease|aaBB) = 0.2, and P(Disease|others) = 0, where A, a, B and b represent the alleles for the disease loci and P(A) = P(B) = 0.3 in these two models * Here we choose u a/2 = 3 as a threshold for the selection of associated SNP patterns…”
Section: Resultsmentioning
confidence: 99%
“…This method is applied to a case-control schizophrenia study from a Chinese Han population to detect the effects of 17 loci of four candidate genes, the regulator of Gprotein signaling-4 (RGS4, 1q21-q22), frizzled 3 (FZD3, 8p21), neuregulin 1 (NRG1, 8p22-p11), and G72 (13q34), on the susceptibility to this disease, since these have been reported in other studies to be possible candidate genes for schizophrenia (Yue et al 2006(Yue et al , 2007Zhang et al 2004;Harrison and Owen 2003).…”
Section: Introductionmentioning
confidence: 99%